King Ivory [videorecording (DVD)] - Swab, John; Dale, James Badge, 1978-; Foster, Ben, 1980-; Cochrane, Rory (Sony Pictures Home Entertainment, 2026)
A gritty action crime thriller about the dangerous underworld of fentanyl cartels in middle America. Work hits too close to home for a drug cop when his son becomes an addict. He makes it his mission to take down those responsible, including the Mexican cartel, Indian Brotherhood War Chief, and the local Irish Mob.